2020
DOI: 10.1037/tra0000682
|View full text |Cite
|
Sign up to set email alerts
|

Disparities, desperation, and divisiveness: Coping with COVID-19 in India.

Abstract: India enforced one of the world's largest lockdowns in the last quarter of March 2020 to minimize the impact of the COVID-19 pandemic. This commentary focuses on the mental health implications of the ongoing pandemic as well as the lockdown that lasted for more than two months and is still in place in certain areas. Whereas loneliness, stress, anxiety, and depression have been widespread, vulnerable sections of the population, including daily wage workers, migrant laborers, religious minorities, women and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…Stressors associated with the COVID-19 outbreak are multi-faceted, unevenly distributed in society, and impact those across the age spectrum (Mukherjee, 2020 ; Prime et al, 2020 ; Fortuna et al, 2020 ). For youth, noted stressors in emerging studies have mostly focused on ramifications of quarantine in the early weeks of the outbreak, including social isolation, changes to routine, and lack of activity.…”
Section: Coping and Mental Health In Early Adolescence During Covid-1mentioning
confidence: 99%
“…Stressors associated with the COVID-19 outbreak are multi-faceted, unevenly distributed in society, and impact those across the age spectrum (Mukherjee, 2020 ; Prime et al, 2020 ; Fortuna et al, 2020 ). For youth, noted stressors in emerging studies have mostly focused on ramifications of quarantine in the early weeks of the outbreak, including social isolation, changes to routine, and lack of activity.…”
Section: Coping and Mental Health In Early Adolescence During Covid-1mentioning
confidence: 99%
“…In order to contain the virus spread, a nationwide lockdown was imposed on March 24, 2020. The country was successful in limiting the number of cases initially with a slew of preventive and containment measures [ 37 ]. However, due to economic and social reasons, the lockdown was gradually eased.…”
Section: Dynamics Of Covid-19 Pandemic In Indiamentioning
confidence: 99%
“…Multiple preliminary studies have demonstrated the prevalence of various common mental health concerns among individuals in India (Ahmad et al., 2020; Saikarthik et al, 2020). Apart from its impact on the general public, the pandemic and lockdown have also disproportionately impacted vulnerable sections of the society and widened existing disparities (Mukherjee, 2020). Some of the groups most affected by the pandemic are daily‐wage earners who depend on their everyday livelihood for survival, migrant workers stuck in their places of work without any income or means of transport to return home, women and children facing increased levels of violence and abuse, persons with pre‐existing mental health concerns facing worsening of issues, and individuals from the queer community having to live with disapproving and sometimes violent families (Golechha, 2020; Singh, 2020a, 2020b; Vora et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The second is related to the challenges faced by those who are providing these services and the support they need. As is evident from the literature (Mukherjee, 2020) and from the nature of calls received by some of the leading helplines in India (Ravindran et al., 2020), concerns experienced by the general public, and especially those belonging to vulnerable sections of the society, are often psychosocial in nature. The distress experienced by individuals is not just rooted in their psyches or in the fear of the infection, but is also rooted in their social and economic contexts.…”
Section: Introductionmentioning
confidence: 99%